Tinjauan Yuridis Ketentuan Tanggal Efektif Pemberitahuan Akuisisi Saham Kepada Komisi Pengawas Persaingan Usaha (Studi Kasus Putusan KPPU Nomor: 05/KPPU-M/2017) - Amalia Fitri Kusuma Dewi; Muhammad Ali Hanafiah Selian (JOURNAL of LEGAL RESEARCH, 2019)
Abstract:The study was conducted to find out how the provisions for the validity of the legal takeover of shares to KPPU and to determine what the consequences of the delay in notification of the takeover of shares to PT. Indonesian Telecommunications Professionals based on applicable regulations. The method used is a qualitative research method with a normative juridical approach by analyzing decisions and related to laws and regulations in the field of Business Competition Law. This study uses a statute approach, a conceptual approach and a case approach. The results showed that the provisions for the validity of a juridical effective date were from the date the notification was received by the Ministry of Law and Human Rights, both in the event of changes in the articles of association and those that were not accompanied by changes in the articles of association. As for notification of takeover of shares to KPPU, it must be done no later than 30 (thirty) days from the legal effective date. As a result of the late announcement of the takeover of shares, PT. Indonesian Telecommunications Professionals are subject to administrative action in the form of fines of Rp. 1,100,000,000.00 (one billion one hundred million rupiah).Keywords: Juridical Effective Date, Late Notification, Share Takeover, Due to Delay